Joint association of the inflammatory marker and cardiovascular-kidney-metabolic syndrome stages with all-cause and cardiovascular disease mortality: a national prospective study - Yifei Cao; Wenfeng Wang; Shidong Xie; Yanfang Xu; Zishan Lin (BMC Public Health)
Abstract Background Cardiovascular-kidney-metabolic (CKM) syndrome and systemic inflammation significantly contribute to mortality. However, the joint associations of CKM stages and systemic inflammation with all-cause and cardiovascular disease (CVD) mortality remain unclear. This study aimed to evaluate the independent and joint associations of CKM stages and systemic inflammation with all-cause and CVD mortality in a representative cohort of United States adults. Methods We analyzed data from 29,459 adults aged ≥ 20 years from the National Health and Nutrition Examination Survey (1999–2018). CKM stages were classified based on metabolic risk factors, CVD, and chronic kidney disease. Systemic inflammation was assessed using multiple indicators, and time-dependent ROC analysis identified the systemic inflammatory response index (SIRI) as the most effective inflammatory marker. The associations of CKM stages and SIRI with mortality were evaluated. Results Over a median follow-up of 109 months, 5,583 all-cause deaths and 1,843 CVD-specific deaths occurred. Both advanced CKM stages and elevated SIRI were associated with higher risks of all-cause and CVD mortality. Individuals with advanced CKM stages (Stages 3–4) and elevated SIRI (> 0.81) had the highest risks of all-cause (HR: 1.84, 95% CI: 1.65–2.05) and CVD mortality (HR: 2.50, 95% CI: 2.00–3.12). These associations were particularly pronounced in adults aged < 60 years (P for interaction < 0.001). Conclusions Advanced CKM stages and elevated SIRI are associated with increased risks of all-cause and CVD mortality, particularly in younger adults. These findings highlight the significance of targeted interventions to address systemic inflammation and CKM progression, potentially improving long-term outcomes in high-risk populations.